Ethics-Based Social Education Benefit from the Perspective of Abid Al-Jabiri - Nikmah Royani Harahap (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This paper examines the concept of social education based on the benefit of the people offered by Abid al-Jabiri in the book Al-'Aql Al-Akhlaqi, Al-'Arabi. This research can be categorized as library research. In this study, the authors used a qualitative approach. The primary source in this research is the book Al-'Aql Al-Akhlaqi, Al-'Arabi by Muhammad Abid Al-Jabiri, which was published in Beirut by the publisher Markaz Dirasat Al-Wihdahal-Arabiyyah in 2001. This study found that the perspective of benefit ethics al-Jabiri emerged because of weaknesses in the previous ethical concept: ethics of al-Tha'ah moral obedience, al-Sa'adah moral happiness ethics, and al-Fana, and al-Muru'ah morality. In addition, the author also finds that the social education offered by al-Jabiri has an ethical concept based on good deeds, as al-Jabiri's opinion in the book Al-'Aql Al-Akhlaqi, Al-'Arabi; In fact, good deeds are central values in ethics that Muslims or Islamic ethics must own. So that with the nature of good deeds in every individual, then benefit or goodness will be born in social life.